CALCULATION OF THE GEOMETRIC PARAMETERS OF THE EJECTION DEVICE THAT ARE USED TO EXTINGUISH THE FIRE: Array - , І. Ф., О. О., А. Я., О. С., Г. В. (Municipal economy of cities. Series: «Economy science», 2018)
For effective use of the technology of extinguishing hot storage tanks of flammable combustible liquids using gel-forming fire extinguishing and flame retardants, the formation of a non-combustible floating layer of granulated foam glass has been proposed, by feeding it to the surface of a burning liquid using an air ejector of an air foamglass type. An engineering method has been developed for calculating the geometric parameters of an air-foamglass type air ejector for supplying granulated foam glass. Using the developed method of calculating the geometric parameters, the axial dimensions of the ejector were calculated, according to which an experimental prototype was made with the following design parameters: the input nozzle section area - 720 mm2; the area of the outlet section of the working nozzle - 380 mm2; cross-sectional area of the mixing chamber - 1550 mm2; length of the mixing chamber - 425 mm; the area of the output section of the mixing chamber is 1800 mm2. The calculation of the geometric parameters of an air-foam glass air-jet ejector made in the article is based on experimental data obtained by the authors, and also takes into account the physical and mechanical properties of the transported material. Further studies of the design and operation of the air-foamglass-type airplanes imply experimental studies of the performance and maximum range of the supply of granulated foamglass. Considering the use of air-foam glass for fire extinguishing, scientific and practical interest is also caused by the proportional composition and behavior of the air-foam glass two-phase air-material flow as it moves along the tubular material lines, as well as when flammable combustible fluid, which requires further analytical and experimental studies. Keywords: ejection apparatus, the axial dimensions of the ejector, performance, design, method of calculation.